Análise semiótica da publicidade de Oliviero Toscani para Benetton - Gera, Karina Spineli (2014)
This thesis aims to find recurrent themes and figures in six different advertising photographs produced by Italian photographer and publicist, Oliviero Toscani for Benetton brand campaigns. The selected images are inserted in the book ―Advertising is smiling carrion‖ (TOSCANI, 2003). To support the, recourse will be made to the theoretical framework of French semiotics and its development of plastic made by semi-semiotic symbolism. The selected images were produced for the collection of the brand United Colors of Benetton between 1989 to 1993 and call for attention just leave the default visual context created by advertising, to show products being used by beautiful people and their screenplays. In opposite to this concept, the images produced by Toscani not bring the advertised product explicitly, in case the clothing brand Benetton. In the images chosen Toscani embeds a social, political and religious discourse. Therefore, we will describe the construction of meanings generated by these objects. Will be broken initially by plastic semiotics and its semi-symbolism. The hypothesis is that the photos in question, although images designed differently, producing symmetrical discourse grounded on a theme where there is recurrence of discursive elements (isotopie), these speeches that are intended to recover and describe. Keywords: photography; advertising; Oliviero Toscani; semiotic-plastic; and semisymbolism.